Cleaning of aviation hydraulic and motor oils from emulsion water and mechanical con-taminants in quazi-permanent electric field - Гаража, B. B.; Халиль, С. А. (Proceedings of National Aviation University (archive), 1999)
Presented are the results of experimental research of cleaning efficiency of aviation hydraulic and motor oils by means of full-scale polarization electrodehydrator from emulsion water and mechanical contaminants under laboratory and industrial conditions